(untitled) (Journal of Economic Research & Business Administration, 2023)
The relevance of this article is due to the need to update the criteria for assessing the effectiveness of public administration for the conditions of Kazakhstan and bring them into line with the best world practices in the digital economy. The purpose of this article is to develop an author’s methodology for assessing the effectiveness of public administration, taking into account the state of the assessment methodology, the trend towards digitalization of the public sector, the opinions of experts and other factors in the Republic of Kazakhstan. The main issue of the study is to determine the most objective criteria for assessing the effectiveness of public administration in the Republic of Kazakhstan in the context of digitalization. The subject of the study is the analysis of methodological approaches to assessing the effectiveness of public administration. The research methodology is based on interdisciplinary, analytical and systematic approaches, as well as methods: desk research, analysis of materials from international organizations, analysis of legal documents of the Republic of Kazakhstan, data from expert surveys, modeling a methodology for assessing the effectiveness of public administration based on strategic analysis (PEST-analysis). As a result of the study, the hypotheses were confirmed: 1) there is a discrepancy between the results of the assessment of the effectiveness of public administration in Kazakhstan by international organizations and the results of the assessment and self-assessment of the state apparatus in the Republic of Kazakhstan; 2) the methodology for assessing the effectiveness of public administration in Kazakhstan needs to be improved, as there is a contradiction between the assessment methods used and the objectivity of the assessment results. Based on the results of the study, the author developed and substantiated a methodology for assessing the effectiveness of public administration in the digital economy for Kazakhstan. The value of the work lies in the deepening of scientific approaches to assessing the effectiveness of public administration in the Republic of Kazakhstan in the digital economy. The practical significance of the study lies in increasing the objectivity of the criteria for evaluating the effectiveness of the activities of state bodies of the Republic of Kazakhstan. Key words: public administration, efficiency, digital economy, efficiency criteria, efficiency assessment methodology